Rational Choice Analysis and Political Party Switching in Nigerian Politics: Beyound Ideological Allegiance - Itakpe, Mohammed Lawal; Efanodor-Obeten, Harriet Omokiniovo (Indonesian Journal of Political Studies, 2025)
The study examines the role of Rational Choice Theory (RCT) in understanding the frequent party switching among Nigerian politicians. It explores the motivations behind these defections, assesses their impact on political stability, governance, and democratic consolidation, and identifies policy recommendations for strengthening political party structures and reducing opportunistic defections. Relying on secondary sources of information and using RCT as a theoretical framework, the study argues that Nigerian politicians often engage in defections based on calculated self-interest, seeking electoral advantage, financial benefits, and political survival rather than ideological realignment. The study further reveals that frequent party defections have contributed to political instability, weakened governance, and slowed democratic development by fostering policy inconsistency, undermining institutional trust, and encouraging voter apathy. To address these challenges, the study proposes policy reforms, including stricter enforcement of anti-defection laws, internal party democracy, ideological reorientation, financial regulation of party politics, and enhanced civic education. The findings highlight the need for systemic reforms to promote a more stable, ideology-driven political system that enhances democratic consolidation in Nigeria.